2003
DOI: 10.2134/jeq2003.9490
|View full text |Cite
|
Sign up to set email alerts
|

Soil Sorption of Acidic Pesticides

Abstract: A model of acidic pesticide sorption in soils was developed from theoretical modeling and experimental data, which initially considered a combination of a strongly acidic pesticide and a variable-charge soil with high clay content. Contribution of 2,4-D [(2,4-dichlorophenoxy) acetic acid] anionic-form sorption was small when compared with molecular sorption. Dissociation of 2,4-D was not sufficient to explain the variation in Kd as a function of pH. Accessibility of soil organic functional groups able to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 30 publications
(43 reference statements)
4
20
0
Order By: Relevance
“…This presumably results from the fact that SCP Ϫ is more water soluble than the neutral SCP species (SCP 0 ) and the electrostatic repulsion of SCP Ϫ from increasingly negatively charged soil surfaces. Similar pH effects have been observed for various organic acids sorbing to soils and sediments [11,13,16,21,29].…”
Section: Influence Of Phsupporting
confidence: 75%
See 1 more Smart Citation
“…This presumably results from the fact that SCP Ϫ is more water soluble than the neutral SCP species (SCP 0 ) and the electrostatic repulsion of SCP Ϫ from increasingly negatively charged soil surfaces. Similar pH effects have been observed for various organic acids sorbing to soils and sediments [11,13,16,21,29].…”
Section: Influence Of Phsupporting
confidence: 75%
“…This can be explained by the relatively complex structures of these compounds, which often contain more than one functional group and frequently are ionizable. The pH and ionic strength have been demonstrated to affect the sorption of ionizable chemicals to soil and sediment [11][12][13][14][15][16], octanol [17], membranes [18], and proteins [19]. Changing the pH leads to protonation or deprotonation of ionizable compounds, thereby changing the physicochemical properties and, subsequently, the sorption of a compound.…”
Section: Introductionmentioning
confidence: 99%
“…A review of studies on modeling of the pH-dependent adsorption of organic acids that were carried out for more than 25 yr by many authors was not the aim of the present study. Details concerning this subject can be found elsewhere [28,44,50,[88][89][90]. This topic merits a brief discussion, however, because the finding that adsorption of 2,4-D, MCPA, dichlorprop, and mecoprop in soils is significantly inversely correlated with their log D values may have significant effects on advances in the prediction of adsorption of these compounds in soils.…”
Section: Aspects Of Modeling the Adsorption Of 24-d Mcpa Dichlorprmentioning
confidence: 99%
“…The increase in the Ca 2þ concentration causes a slight increase in the adsorption of anions of phenoxyalkanoic acid herbicides on organic matter, kaolinite, and quartz through a Ca-bridging mechanism [50,75]. Despite this, an increase of pH in the plough layer of arable soil, which is the result of liming [167], decreases the adsorption of phenoxyalkanoic acid herbicides [20,38,88] because the affinity of organic matter for the anionic form is at least 10 times less than that for the neutral forms of these compounds [27,44,50]. A study by McGhee and Burns [109] indicated that liming slightly inhibited the degradation rate of 2,4-D and MCPA in soils.…”
Section: Influence Of Liming and Fertilizers On Leachingmentioning
confidence: 99%
“…A large number of experimental investigations has addressed the sorption and/or desorption of phenoxyalkanoic acid herbicides in soils, and on individual soil components or various inorganic sorbents (see Hermosin & Cornejo, 1993;Benoit et al, 1996;Haberhauer et al, 2000;Spadotto & Hornsby, 2003). It was observed that some electrolytes in solutions have an important impact on the sorption behaviour of phenoxyacetic acids on clay minerals.…”
Section: Introductionmentioning
confidence: 99%